The role of intimal hyperplasia in arterial spasm. - McGregor, M (1984)
It has been postulated that even moderate spasm in an artery with intimal hyperplasia can produce organ hypoxia because there is an excessive reduction in the diameter of the lumen. To test this hypothesis we created intimal hyperplasia in one femoral artery in five pigs and then induced arterial spasm by administering ergonovine maleate. Arterial spasm did not produce a greater reduction in the luminal diameter of the femoral artery with intimal hyperplasia than it did in the normal femoral artery. Until further evidence appears this hypothesis must be viewed with caution.